Unnatural Death - Cornwell, Patricia Daniels (United States : Sphere, 2023)
"Chief medical examiner Dr. Kay Scarpetta finds herself in a Northern Virginia wilderness examining the remains of two campers wanted by federal law enforcement. The victims have been savaged beyond recognition, and other evidence is terrifying and baffling, including a larger-than-life footprint. After one of the most frightening body retrievals of her career, Scarpetta must discover who would commit murders this savage, and why."--
Keywords: Medical Examiners (Law); Forensic Pathologists; Women Physicians